Evaluating the Blue Economic Potential of the Invasive Alien Macroalga Stypopodium schimperi - Ergenler, Aysegul; Zaman, Buse Tugba; Bozkir, Elif; Aydin, Zekiye Ceren Arituluk; Siyah, Pinar; Karakurt, Serdar; Bakirdere, Sezgin; Depci, Tolga; Turan, Funda (SPRINGER INT PUBL AG, 2026)
The rise in global demand, coupled with growing environmental concerns, necessitates the identification of new energy sources that can support socioeconomic development while minimizing pollutant emissions. Aquatic biomasses, particularly invasive aquatic seaweeds, may serve as viable bioeconomic resources. This study seasonally evaluated the nutrient composition, elemental content, essential and nonessential metal contents, and overall characterization of the invasive macroalga Stypopodium schimperi to assess its potential as a value-added biomass and bioeconomic resource. Regarding the Fourier-transform infrared spectroscopy (FT-IR) analysis, various characteristic peaks were observed over a wide wavelength range in the IR spectrum. Examination of the main peaks revealed broad and strong bands in the range of 3500-3200 cm(-)& sup1;, indicating that the invasive alien macroalga S. schimperi contains numerous organic molecules such as polysaccharides, proteins, lipids, and phenolic compounds. The present study showed that the invasive macroalga S. schimperi represents a rich biomass source of essential metals such as Ca, Mg, Ni, Zn, Cu, and Fe. In addition, the detection of only low quantities of toxic or nonessential metals (Pb, Cd, Hg) suggests its potential safety for use in the food industry or biotechnological applications. The elemental composition of S. schimperi collected during the summer season was determined to be 35.63 +/- 0.51% C, 5.14 +/- 0.16% H, 1.58 +/- 0.20% N, 0.41 +/- 0.05% S, and 57.24 +/- 0.57% O. For samples collected in the autumn season, the elemental composition was 35.28 +/- 0.49% C, 5.08 +/- 0.26% H, 1.51 +/- 0.26% N, 0.45 +/- 0.06% S, and 57.69 +/- 0.50% O.Furthermore, this study generally observed that S. schimperi has moderate levels of protein and carbohydrates, low levels of lipids, and high moisture content in terms of nutritional composition, suggesting that this species could be used as a raw material in functional foods, feed additives, or biotechnological applications, within the framework of the Blue economy.
Keywords: Blue economy; Marine resources; Macrophytes; Value-added biomass; FATTY-ACID PROFILE; BIOCHEMICAL-COMPOSITION; BROWN SEAWEEDS; COAST; EXTRACTION; SEA; BAY; POLYSACCHARIDES; MEROTERPENOIDS; PROXIMATE; Marine & Freshwater Biology; Oceanography